Reading is for girls!? The negative impact of preschool teachers' traditional gender role attitudes on boys' reading related motivation and skills - Wolter, Ilka; Braun, Edith; Hannover, Bettina (Frontiers in Psychology, 2015)
According to gender stereotypes, reading is for girls. In this study, we investigated the role of preschool teachers in transmitting such gendered expectations. We suggest that boys are less motivated to read in preschool, and less competent in reading one year later in primary school, if their preschool teacher holds a traditional gender role attitude than if the teacher has egalitarian beliefs. In 135 independent dyads of a female preschool teacher (N=135) and one boy (n=65) or one girl (n=70) we measured teacher's gender role attitude, child's reading related motivation as well as precursors of reading skills in preschool, and child's reading skills at the end of first grade in primary school. As expected, the more traditional preschool teachers' gender role attitude was, the weaker was boys' motivation to (learn to) read while girls' motivation was unrelated to teachers' gender role attitude. In either gender, motivation in preschool predicted reading skills at the end of first grade.